2020
DOI: 10.1002/saj2.20153
|View full text |Cite
|
Sign up to set email alerts
|

Field‐scale apparent soil electrical conductivity

Abstract: Soils are notoriously spatially heterogeneous and many soil properties are temporally variable. Spatial variability of soil properties has a profound influence on agricultural and environmental processes, such as plant–water–soil interactions, water flow, and solute transport, resulting in within‐field plant yield variation and degradation of soil quality, to mention only a few. Field‐scale mapping of spatial variability and monitoring of temporally dynamic soil properties is necessary for a variety of edaphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 160 publications
2
20
0
Order By: Relevance
“…Regarding the soil's percentages of sand, silt, and clay, as shown in Table 3, the results revealed that Z2 and Z3 presented higher contents of clay and lower of sand, significantly contrasting with Z1. This outcome is in accordance with the above results, since soils with high clay contents are expected to have higher CEC [22], as the exchange surfaces in clay minerals adsorb exchangeable cations and consequently increase exchangeable cations that can be exchanged and absorbed by the plants. This relationship has already been studied using remote data, showing the strong correlation between EC ap and clay content and CEC, concerning all types of EC ap data and across a multitude of fields [23].…”
Section: Resultssupporting
confidence: 90%
“…Regarding the soil's percentages of sand, silt, and clay, as shown in Table 3, the results revealed that Z2 and Z3 presented higher contents of clay and lower of sand, significantly contrasting with Z1. This outcome is in accordance with the above results, since soils with high clay contents are expected to have higher CEC [22], as the exchange surfaces in clay minerals adsorb exchangeable cations and consequently increase exchangeable cations that can be exchanged and absorbed by the plants. This relationship has already been studied using remote data, showing the strong correlation between EC ap and clay content and CEC, concerning all types of EC ap data and across a multitude of fields [23].…”
Section: Resultssupporting
confidence: 90%
“…Variables such as topography, and apparent electrical conductivity (ECa), which can be collected in the field using soil sensors, can be useful to predict grain quality. Apparent electrical conductivity is a measure of conductivity of soils and is influenced by texture, water content, organic matter, cation exchange capacity, and salinity, which are known to influence crop yield (Corwin & Scudiero, 2020;Kitchen et al, 2003). Topography plays a critical role in variations in soil moisture and nutrient content, which affect crop yield and quality (Hawley et al, 1983;Kravchenko & Bullock, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This parameter's value can depend on several factors related to the soil's intrinsic properties and management. In agricultural soils, factors such as the climatic trend, irrigation water quality and fertilization could significantly affect soluble salts concentration in the soil [54,55]. Among vegetable crops, the onion is a species that is highly susceptible to salinity [21,56].…”
Section: Chemical Soil Parameters and Fresh Onion Yieldmentioning
confidence: 99%